Analysis of CTD Parameters in Bawean Waters Using 3D Modeling - Khoirunnisaa, Avly Arfiani; Minsaris, La Ode Alam; Rosalia, Ayang Armelita; Wulansari, Nadia Zahrina (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Bawean waters, located in the Java Sea about 150 km north of Gresik, East Java Province, have complex oceanographic characteristics that are interesting to study. The biodiversity and oceanographic conditions of its waters are influenced by hydrodynamic factors, such as ocean currents, tides, and other physical and chemical parameters. This study aims to analyze the oceanographic characteristics of the waters around Bawean Island based on the parameters of temperature, salinity, density, conductivity, and sound speed that play a role in the dynamics of the water mass. Measurements were made using CTD (Conductivity, Temperature, and Depth) instruments with the Direct Reading method, which allows real-time analysis of water masses. The data obtained was then processed using Ocean Data View (ODV) software to identify the distribution patterns of oceanographic parameters. In addition, Surfer software was used in modeling the three-dimensional visualization of oceanographic parameter density distribution patterns. The study sites were categorized into three zones, namely near land, far land, and perpendicular to land, to understand the differences in parameter distribution in different areas. The results showed that the water temperature was in the range of 28.75°C-31.25°C, salinity 26-33.1 PSU, conductivity 45-55 µS/cm, density 1016-1021 kg/m³, and sound speed 1534-1543 m/s. The modeling results and contour maps show that there is a connected density distribution pattern from the causation of low temperature parameters that affect the increase in salinity, conductivity, density, and decrease in sound speed. In addition, this research is expected to provide an in-depth understanding of the distribution patterns, distribution of oceanographic parameters in the waters of Bawean Island and the influence of factors that affect them.